2018
DOI: 10.1002/pola.29087
|View full text |Cite
|
Sign up to set email alerts
|

Poly‐p‐phenylenevinylene‐g‐poly(2‐(methacryloyloxy)Ethyl)trimethylammonium chloride (PPV‐g‐PMETAC): A fluorescent, water‐soluble, selective anion sensor

Abstract: The photophysical and ion-sensing properties of densely grafted conjugated polymer poly-p-phenylenevinyleneg-poly(2-(methacryloyloxy)ethyl)trimethylammonium chloride (PPV-g-PMETAC) are presented herein. The grafted polymer exhibits excellent iodide-sensing which is easily observed using fluorescence spectroscopy. The iodide detection limit for PPV-g-PMETAC was found to be 10 nM and was independent of temperature and pH <12. The change in fluorescence of PPV-g-PMETAC, upon exposure to iodide, was attributed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…These properties enable CPs becoming the most suitable candidates for optical chemical sensing of iodide ions. It has also been found that the shifting of responsive units from the backbone of polymer and grafting them to the brushes can result in stimulus‐responsive and smart materials of particular interest to be utilized for environmental, biological, and pharmaceutical applications [125] …”
Section: Challenges and Future Aspectsmentioning
confidence: 99%
See 2 more Smart Citations
“…These properties enable CPs becoming the most suitable candidates for optical chemical sensing of iodide ions. It has also been found that the shifting of responsive units from the backbone of polymer and grafting them to the brushes can result in stimulus‐responsive and smart materials of particular interest to be utilized for environmental, biological, and pharmaceutical applications [125] …”
Section: Challenges and Future Aspectsmentioning
confidence: 99%
“…It has also been found that the shifting of responsive units from the backbone of polymer and grafting them to the brushes can result in stimulus-responsive and smart materials of particular interest to be utilized for environmental, biological, and pharmaceutical applications. [125] * The new nanomaterials with enzyme-like characteristics termed nanoenzymes also have great potential in the The construction of four complexes 1-4, in which complexes 1-3 may be utilized for the fluorometric determination of iodine ions. [133] Copyright © Royal Society of Chemistry, 2015.…”
Section: Challenges and Future Aspectsmentioning
confidence: 99%
See 1 more Smart Citation
“…If the backbone of BBPs is a conjugated polymer, the stimuli-induced collapse of polymeric side chains can modulate the electronic structure of the backbone, resulting in changes in the optical property, which could be employed for sensing. Using the ATRP grafting from approach, Balamurugan et al and Wang et al synthesized thermoresponsive PNIPAM-grafted (PT- g -PNIPAM) and pH-responsive PDMAEMA-grafted polythiophene BBPs (PT- g -PDMA), respectively; , noticeable shifts in the absorption wavelength of the polythiophene backbone were observed when external stimuli were applied to expand or shrink the side chains. For example, Wang et al reported that PT- g -PDMA in water showed a red shift of 18 nm in the maximal absorption (λ max,abs ) when the solution pH was decreased from 8 to 2 (Figure a,b) and the color of the solution changed from yellow to dark orange (Figure c) .…”
Section: Environmentally Induced Shape Transitions Of Bbps With a Sin...mentioning
confidence: 99%
“…Despite the progress, more effort is still needed to further understand the coupled influences of various molecular parameters on the transitions of multicomponent BBPs between different conformations or morphologies. Almost all explicit dramatic shape transitions, such as wormlike/starlike-to-globular, reported in the literature so far are achieved with the use of the BBPs made from a flexible poly­(meth)­acrylate backbone. Stimuli-responsive BBPs composed of a conjugated polymer backbone, e.g., polythiophene, and responsive polymeric side chains have been reported; although worm-to-globule shape transitions were proposed for the brushes to respond to environmental stimuli, the experimental verification was complicated by the intermolecular aggregation of brush molecules . If the worm/rod-to-globule shape transition is unequivocally confirmed by AFM or TEM, the family of stimuli-responsive shape-changing polymers would be greatly expanded. Synthesis of well-defined BBPs with multicomponent side chains remains a challenge.…”
Section: Challenges and Outlook In The Design Synthesis Characterizat...mentioning
confidence: 99%